Acute Benign Myositis of Childhood Associated with Influenza B Virus: Case Report - M. Afonso, Ana Rita; R. Antunes, Catarina; Geraldes, Nicole (Gazeta Médica, 2025)
Benign acute childhood myositis (BACM) is a rare complication associated with viral respiratory infections, with the Influenza B virus being the most frequent agent. The disease typically begins with nonspecific symptoms, such as fever, headache, rhinorrhea, and fatigue, progressing to severe myalgias in the lower limbs. Diagnosis is clinical, and treatment is symptomatic, focusing on hydration to prevent acute kidney injury due to myoglobinuria.A seven-year-old child presented with asthenia, fever, odynophagia, and rhinorrhea, which progressed to myalgias and an inability to walk. Following confirmation of the diagnosis of myositis, the child was hospitalized for treatment with fluid therapy and oseltamivir. This case highlights the importance of early recognition of BACM, especially during influenza outbreaks, to prevent complications and provide appropriate treatment, which is reassuring for the family.